Analyzing Poverty Reduction Through ZIS, Inflation, and Economic Growth - Rosyidah, Norma; Luthfiyah (Universitas Airlangga, 2025)
Poverty is one of the country's most difficult economic problems. Poverty showed a significant number when the pandemic occurred at the end of 2020, and there were 27.55 million people who were below the poverty line. After the pandemic, economic activity gradually improved, so poverty in Indonesia declined. One of the steps to reduce poverty is to analyze which economic instruments can be optimized. This study aims to determine the effect of the distribution of zakat, infaq, and alms (ZIS) funds, inflation, and economic growth on poverty in Indonesia for the period 2012-2022. This research uses quantitative methods with multiple linear regression analysis. The data processing tool used is SPSS. The T-test results show that the distribution of ZIS funds significantly affects the poverty rate. In contrast, inflation and economic growth do not have a significant effect on the poverty rate partially. The F-test shows that the distribution of ZIS funds, inflation, and GDP significantly affect the poverty rate simultaneously in the period 2012-2022. The limitation of this study is the use of variables that affect poverty rates, so future researchers should add or change these variables to other variables related to poverty. This research implies that BAZNAS, as a national amil zakat institution, can develop its program better so that through the distribution of ZIS, the poverty rate in Indonesia can be reduced.